HEALTH LEVEL ANALYSIS OF PT. BANK BJB USING THE CAMEL METHOD - Wildan Army Abdillah; Muhammad Iqbal Nurfauzan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
AbstractThis study aims to assess the financial soundness level of Regional Development Bank of West Java and Banten (PT. Bank BJB) during the 2012-2021 period using the CAMEL method. The CAMEL method is used to assess the financial aspects of a financial institution, namely Capital, Asset Quality, Management, Earnings, and Liquidity. This study uses a quantitative approach with a descriptive method, which is carried out by analyzing data from the financial report sources of PT.Bank  BJB during the 2012-2021 period. The data used in this study are secondary and are analyzed using various financial analysis techniques. The study results indicate that the financial soundness of Regional Development Bank of West Java and Banten (PT. Bank BJB) during the 2012-2021 period can be stated to be very healthy. This can be the basis for managers to predict the bank's financial condition in the future and take appropriate policies to improve the bank's financial performance. This research has an essential meaning because the level of the financial health of a financial institution can reflect how the bank implements its economic policies.Keywords: Assets, Capital, Earnings, Liquidity, Management